Branding strategy formulation for Ã¢â‚¬Å“futlimeÃ¢â‚¬Â in order to raise its revenue growth - Hafiyyan Supriyo Suromo, Dera; Dhewanto, Wawan (The Indonesian Journal of Business Administration, 2016)
Abstract- Nowadays, there are many internet users in Indonesia. In 2015, according to Ã¢â‚¬Å“we are socialÃ¢â‚¬Â, there are 72.7 million active internet users. And there are 5.9 million people who had shopped online in Indonesia (SingPost, 2014). The numbers have been increasing every year. Besides that, the tendency to celebrate the special moment by giving gift is also growing in Indonesia which are 79 % Indonesia people doing this (Groupon, 2014). Because of these opportunities, Futlime was found by Dera Hafiyyan S.S. and Vanessa Lidya L. in 2013. Futlime produces and offers various unique gifts to the customers who want to celebrate their special moments through online marketing. Because the gift industry is potential and growing industry,Ã‚Â  there are many competitors for Futlime. It causes the revenue grows slowly. It will be worse and cause Futlime cannot survive in gift industry competition, if Futlime does not take the action to solve it soon. For the limitation, this research only discusses about developing business solutions, especially branding strategy for Futlime to increase the revenue growth by customer based on brand equity analysis and creating marketing communication. In this research, business environment analysis of Futlime is conducted by using PESTEL analysis, PorterÃ¢â‚¬â„¢s Five Forces, value chain analysis, and VRIO framework. The root causes of decreasing in revenue growth are founded, which is unclear strategies for every aspect of the business, especially in branding. The problem makes Futlime unable to face threats and take advantage from many opportunities. That is why this research will be focused on creating marketing communication for Futlime based on the consumerÃ¢â‚¬â„¢s behavior and mind set. In order to create the right marketing communication for Futlime, it will be needed to know and explore the mind set of FutlimeÃ¢â‚¬â„¢s current and potential costumer deeply. In this research, to study the current and potential costumerÃ¢â‚¬â„¢s mind set, brand knowledge questionnaire is used. Based on the result of the questionnaire, Futlime has enough brand awareness. However, it is still not enough to capture market in the potential industry likes gift industry. So, Futlime has to increase the brand awareness. Futlime does have the right brand association in customer mind set. They also love the company products and service, especially the good and customized design. However, Futlime has three main shortages which are the expensive price and lack of marketing. These shortages have to be explored further and solved. Futlime also has good achievement like the respondents tendency to be happy. Furthermore, they want to recommend Futlime to others. This condition has to be maintained to gain the effect of mouth to mouth marketing. To create strong brand awareness for Futlime, marketing mix that is appropriate with the target audience of Futlime is online forum and social media advertising, especially Instagram (most used media social based on the questionnaire). The marketing communication for Futlime will be divided inti two part. The objective for the first part is getting 2099 new followers per month orÃ‚Â  12.594 followers in 6 months. It will be 126 advertising during 6 months, with 21 advertising per month.Then, the objective for the second part is getting 2475 new followers per month or 29.700 followers in a year. It will be 297 advertising during a year, with 25 advertising per month. The total cost of advertising is Rp 81.450.000. Other than that, to boost sales and solve the expensive price mindset, the company will be supported by sales promotion. Based on the questionnaire, the promotion that is loved by FutlimeÃ¢â‚¬â„¢s target audience is special day promo.Ã‚Â Keywords: online gift store, brand knowledge, marketing communication, SWOT analysis, brand value chain, branding strategy.